2009
DOI: 10.4028/www.scientific.net/kem.410-411.481
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Specimen Dimensions on Obtained Tensile Properties of Sheet Metals

Abstract: A pilot study has been carried out to examine the effect of specimen dimensions on the obtained tensile properties of aluminium and steel sheet. The materials used were DP600 grade steel and AA5754 grade aluminium sheet. Four types of dog-bone samples with varying dimensions were tested for both materials. Standard tensile test procedures were performed using a universal test machine together with contacting extensometry. The GOM Aramis photogrammetric 2D strain mapping technique was also applied. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The flow curves matched up to the uniform elongation, that is, when the UTS was reached, and when localized deformation beyond uniform deformation occurred, there were significant deviations with major elongation reduction in the flat specimen flow curve. Different works [62,63] on the effects of flat tensile specimen geometry on mechanical properties have reported that the tensile flow curves were comparable to UTS as long as tensile specimen geometry complied with international standards. In [64], flow curves from round and flat specimens of a ferritic-pearlitic steel have reported the same results found in nickel in Figure 22, with good matching of the tensile flow curves up to UTS and significant deviation after localized deformation.…”
Section: Tensile Behavior Of 25 MM Y-blocks With Round Tensile Specim...mentioning
confidence: 89%
“…The flow curves matched up to the uniform elongation, that is, when the UTS was reached, and when localized deformation beyond uniform deformation occurred, there were significant deviations with major elongation reduction in the flat specimen flow curve. Different works [62,63] on the effects of flat tensile specimen geometry on mechanical properties have reported that the tensile flow curves were comparable to UTS as long as tensile specimen geometry complied with international standards. In [64], flow curves from round and flat specimens of a ferritic-pearlitic steel have reported the same results found in nickel in Figure 22, with good matching of the tensile flow curves up to UTS and significant deviation after localized deformation.…”
Section: Tensile Behavior Of 25 MM Y-blocks With Round Tensile Specim...mentioning
confidence: 89%